1996
DOI: 10.1111/j.1476-5381.1996.tb16006.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human basophil function by phosphatase inhibitors

Abstract: Okadaic acid, a cell permeant inhibitor of protein serine/threonine phosphatases (PPs), attenuated the IgE‐mediated release of the pre‐formed mediator, histamine from human basophils in a time‐ and dose‐dependent manner. Optimal inhibition (77 ± 4%, P < 0.0001) of histamine release was observed following a 2 h incubation with 1 μm okadaic acid. Okadaic acid and two analogues of okadaic acid were also studied and were found to inhibit the IgE‐dependent release of histamine. Concentrations required to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Our own previous studies have shown that okadaic acid inhibits the stimulated release of mediators from human lung mast cells (HLMC) suggesting that PPs may regulate HLMC responses (Peachell & Munday, 1993). Similar studies in rat peritoneal mast cells (Takei et al, 1993;Estevez et al, 1994), rat basophilic leukaemia cells (Sakamoto et al, 1994) and human basophils (Botana & MacGlashan, 1993;Peirce et al, 1996) have also been reported. In the present work we have attempted to characterize PP activities in HLMC and to determine whether okadaic acid inhibits HLMC responses by interacting with PPs.…”
Section: Introductionsupporting
confidence: 80%
“…Our own previous studies have shown that okadaic acid inhibits the stimulated release of mediators from human lung mast cells (HLMC) suggesting that PPs may regulate HLMC responses (Peachell & Munday, 1993). Similar studies in rat peritoneal mast cells (Takei et al, 1993;Estevez et al, 1994), rat basophilic leukaemia cells (Sakamoto et al, 1994) and human basophils (Botana & MacGlashan, 1993;Peirce et al, 1996) have also been reported. In the present work we have attempted to characterize PP activities in HLMC and to determine whether okadaic acid inhibits HLMC responses by interacting with PPs.…”
Section: Introductionsupporting
confidence: 80%
“…An attractive feature of okadaic acid is that it is cell‐permeant and this property has been exploited advantageously to establish whether PPs might be involved in regulating cellular processes (Haystead et al , 1989; Hardie et al , 1991; Hardie, 1993). We, ourselves, have studied okadaic acid, and have shown it to be an effective inhibitor of IgE‐mediated histamine release from HLMC (Peachell & Munday, 1993; Peirce et al , 1997) and basophils (Peirce et al , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported that okadaic acid is an effective inhibitor of mediator release from human lung mast cells (HLMC) and basophils (Botana & MacGlashan, 1993; Peachell & Munday, 1993; Peirce et al , 1996, 1997). Moreover, we have reported that extracts of HLMC and basophils contain PP activities which are sensitive to okadaic acid.…”
Section: Introductionmentioning
confidence: 99%